Geochemical characteristics of geothermal fluids in Thermopigi - Sidirokastro area (Strymon basin, Macedonia) - ΑΡΒΑΝΙΤΗΣ, Α.; ΦΥΤΙΚΑΣ, Μ.; ΚΑΒΟΥΡΙΔΗΣ, Θ.; ΚΑΡΥΔΑΚΗΣ, Γ. (Bulletin of the Geological Society of Greece, 2001)
.The geothermal waters (T>29°C) in the Thermopigi-Sidirokastro area are classified in Na(Ca)-HC03 type and the cold waters in Ca(Mg)-HC03 type. The lower temperature waters have a similar chemical type with the geothermal ones. The geothermal waters have high concentrations in S04 2" and F ions. The Si02 contents range from 28 to 75 mg/ 1. The presence of Ca2+ seems to be related with the marbles and travertines. There is no relationship between components and temperature. The geothermal waters contain C02 and they are slightly saturated in calcite. By using chemical geothermometers it is found that the deep temperature is estimated in 100 °C.